Genetic diversity of Rhododendron dauricum based on morphological traits and SSR markers - Wang, Dan; Ma, Ying; Zhao, Xueli; Wang, Ling (Frontiers in Plant Science, 2025)
Rhododendron dauricum L. is one of the most important ornamental plants in Northeast China for its beautiful flowers. Wild R. dauricum populations are mainly distributed in Greater and Lesser Khingan Mountains in Heilongjiang, China. The diversity of R. dauricum germplasm resources in these areas has not been determined and it can be dynamic due to increasing climate change and human activities, which poses a challenge to effective conservation efforts. To promote genetic diversity conservation and develop new R. dauricum varieties, we performed a systematic morphological and molecular evaluation of R. dauricum populations in the in 13 populations. The results showed significant inter- and intra-population variations. Clustering revealed 3 major groups. Importantly, plants showing extreme variations in flower color and flower number were used to further develop two new cultivars 'Ao Xue' and 'Yanricai', respectively. In addition, nine SSR markers exhibited polymorphism among the 13 populations, and 25 alleles were found. The Shannon information index (I) was 0.6359, and the polymorphism information index (PIC) was 0.3460. The genetic diversity index (Nei's) was 0.3575, and the observable heterozygosity (Ho, 0.2514) was lower than the expected heterozygosity (He, 0.3722). The average genetic differentiation coefficient (Fst) among populations was 0.6556. Several populations with relatively high genetic diversity including Huzhong, Tahe, and Hongxing were identified. We also found that SSR-based clustering generally follows the geographical distances among the populations. Lastly, we identified two SSR markers that were highly correlated with flower color and leaf aspect ratio. Together, our data provided useful information on the germplasm distribution and variation evolution of R. dauricum, which will be valuable for cultivar improvement, protection, and future diversity conservation efforts.